Assessment of endothelial damage and cardiac injury in a mouse model mimicking thrombotic thrombocytopenic purpura. (28th September 2016) - Le Besnerais, M.; Favre, J.; Denis, C. V.; Mulder, P.; Martinet, J.; Nicol, L.; Levesque, H.; Veyradier, A.; Kopić, A.; Motto, D. G.; Coppo, P.; Richard, V.; et al.
Abstract : Essentials Endothelial injury is thought to be a key event in thrombotic thrombocytopenic purpura (TTP). Endothelial and cardiac damages were assessed in a model of TTP using ADAMTS‐13 knockout mice. Damages of cardiac perfusion and function were associated with nitric oxide pathway alteration. Endothelial dysfunction constitutes a critical event in TTP development and cardiac injury. Summary: Background: Cardiac alterations represent a major cause of mortality in patients with thrombotic thrombocytopenic purpura (TTP). Endothelial injury remains poorly defined, but seems to be a key initiating event leading to the formation of platelet‐rich thrombi in TTP patients. Objectives: To assess the changes in endothelial function and the induced cardiac damage in a mouse model of TTP. Patients/methods: We used an animal model in which TTP‐like symptoms are triggered by injection of 2000 units kg −1 of recombinant von Willebrand factor in ADAMTS‐13 knockout mice. Results: These mice developed TTP‐like symptoms, i.e. severe thrombocytopenia, schistocytosis, and anemia. On day 2, magnetic resonance imaging demonstrated a decrease in left ventricular perfusion associated with alteration of left ventricular ejection fraction, fractional shortening, and cardiac output, suggesting early systolic dysfunction. This was associated with decrease in endothelium‐mediated relaxation responses to acetylcholine in mesenteric and coronary arteries, demonstrating severe early endothelial dysfunction. In parallel, we showed decreased cardiac expression of endothelial nitric oxide (NO) synthase and increased expression of antioxidant enzymes, suggesting alteration of the NO pathway. At this time, cardiac immunohistochemistry revealed an increase in the expression of VCAM‐1 and E‐selectin. Conclusion: This study provides evidence that the heart is a sensitive target organ in TTP, and shows, for the first time, strong mesenteric and coronary endothelial dysfunction in an induced‐TTP model. The mechanisms incriminated are the occurrence of a pro‐oxidant state, and proadhesive and proinflammatory phenotypes. This previously largely unrecognized vascular dysfunction may represent an important contributor to the systemic organ failure occurring in TTP.